Debt Stabilization and Debt Mutualization in a Monetary Union with Endogenous Risk Premia - Jacob Engwerda; Bas van Aarle; Arie Weeren (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper we analyse debt stabilization in a monetary union that features endogenous risk premia. In particular, we analyse debt stabilization in two diametrically opposed regimes. In the first regime, the “national fiscal discipline regime”, financial markets impose sovereign risk premia based on each country's government debt level. In the second regime, the “eurobondsRegime”, financial markets impose a risk premium based on the average debt level in the mone-tary union. We compare outcomes in both regimes using simulations of a number of relevant scenarios.
Keywords: C32; H63; H68; H81; 330; Eurobonds; sovereign debt sustainability; sovereign debt crisis